KAJIAN KUALITAS NUTRISI AMPAS KELAPA FERMENTASI (Cocos nucifera L) MENGGUNAKAN EFECTIVE MICROORGANISM-4 DENGAN LEVEL YANG BERBEDA - Danang Biyatmoko; Syarifuddin Syarifuddin; Lilis Hartati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
This study aims to analyze the nutrient content of coconut pulp fermented dregs tocrude protein content, crude fiber and crude fat with different levels of EM-4. The research method used was a complete randomized design (RAL), with four treatments and five replications, in which each replication consisted of a topless container of fermentation. The observed variables were crude protein, coarse fiber and crude axle. Data were analyzed using variance after previously conducted homogeneity test data. If the variance analysis shows a real effect then proceed with the test of the difference of the middle value using the BNT Test. The results showed that the nutrient content of the fermented coconut pulp to the crude protein content increased, while the crude fiber content and crude fat decreased, thus showing very different values significantly (p <0.01).